THE SPECIFIC SOCIAL INFLUENCES ON THE DEVELOPMENT OF ANXIETY-DEPRESSIVE DISORDERS IN ADOLESCENTS - Ochilov Ulugbek Usmanovich (Scholar Express Journals, 2022)
This article is devoted to an important contemporary problem - depressive spectrum disorders in adolescents. It is shown that the problem of depressive disorders of adolescence remains relevant at present. It is noted that adolescent depression is nosologically nonspecific and one of the most frequent manifestations of mental pathology in adolescents. There is a tendency to an increasing number of severe, atypical and masked forms of depression, causing difficulties in diagnosis and adequate therapy. Affective disorders can occur in isolation or in combination with other psychopathological manifestations. Different mechanisms are involved in the formation of these conditions, and their prognosis depends to a greater extent on which nosology, psychological and personality components are involved. The available literature does not provide a clear clinical description of the symptoms of this disorder, as affective pathology is a heterogeneous group of disorders. This makes it difficult to understand the process and structure of the disorder.
Keywords: Depressive Disorders; Suicidal Behaviour; Suicide